Effect of Psychological Intervention on Pelvic Floor Function and Psychological Outcomes After Hysterectomy - Xie, Meilian; Huang, Xin; Zhao, Shan; Chen, Yingtong; Zeng, Xiuqun (Frontiers in Medicine, 2022)
Background: Hysterectomy is one of the most frequently performed operations worldwide. However, postoperative complications and body image changes may induce psychological distress after hysterectomy. The study aimed to evaluate the effect of psychological intervention on pelvic floor function and psychological outcomes following hysterectomy among patients with benign indications. Methods: Ninety-nine patients underwent hysterectomy were randomly divided into intervention group (n=50) and control group (n=49). Patients in the control group received routine postoperative nursing care, while extra psychological intervention was provided to patients in the intervention group, including psychological support, regular lectures and family support. After 6 months, patients’ psychological statuses were assessed by Generalized Anxiety Disorder scale (GAD-7) and Patient Health Questionnaire-9 (PHQ-9). The pelvic floor function of patients was evaluated using Pelvic Floor Impact Questionnaire (PFIQ-7) and Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire (PISQ-12). Furthermore, the incidence of postoperative complications, including uracratia, pelvic organ prolapses, sexual dysfunction and chronic pelvic pain, was evaluated. Results: After 6-month intervention, the GAD-7 and PHQ-9 scores were significantly decreased in the intervention group (p<0.001 and p=0.018 respectively). Both scored were significantly lower than that in the control group (p<0.001 and p<0.001). Compared with control group, the incidence of uracratia, pelvic organ prolapse, sexual dysfunction and chronic pelvic pain for intervention group was significantly lower (p=0.003, p=0.027, p=0.001, p=0.002 respectively) and the pelvic floor muscle strength was significantly stronger (p=0.001). Besides, the postoperative Urinary Incontinence Impact Questionnaire (UIQ-7), Pelvic Organ Prolapse Impact Questionnaire (POPIQ-7), and Colorectal-Anal Impact Questionnaire (CRAIQ-7) scores were significantly lower (p=0.025, p=0.04, p<0.001) and PISQ-12 score was significantly higher in intervention group (p<0.001). Conclusion: Psychological intervention could effectively improve the psychological condition of patients with hysterectomy, which may facilitate patients' postoperative recovery in pelvic floor function. These findings emphasized the necessity of psychological intervention in routine postoperative nursing care.